Indonesia’s Cultural Diplomacy Efforts through Batik in South Korea - Agung Suhabi Putra; Ayuni Nur Siami; Widyanti Tanaijo; Ainniy Zakiyyah Wartabone (Journal of Governance and Global Studies, 2025)
This research discusses Indonesia's cultural diplomacy efforts through batik in South Korea, as part of Indonesia's foreign policy. Batik, as an intangible cultural heritage recognized by UNESCO, has become an important tool to introduce Indonesian culture to the international community. Through various promotional activities, including exhibitions and collaborations with K-pop influencers, Indonesian batik has attracted the attention of the South Korean public. This research aims to analyze the strategies used by the Indonesian Embassy in Seoul in promoting batik, as well as the impact of cultural cooperation between the two countries. The research method used is descriptive qualitative, with data collection through interviews and observations. The results showed that batik diplomacy efforts not only increased awareness of Indonesian culture but also positively contributed to the economic growth and trade of batik in South Korea. This research is expected to provide deeper insights into the role of batik in bilateral relations between Indonesia and South Korea as well as batik copyright protection as part of Indonesia's cultural identity.